Hungarian Accounting Regulations: Exposed to the Cross-Fire - Rita Ambrus; Katalin Borbély (Zeszyty Teoretyczne Rachunkowości, 2015)
The aim of the paper is to highlight two factors influencing Hungarian accounting regulations: the legislation of accounting in the last 25 years and the most important features of the taxation system. Both of them can influence the main requirement of the Hungarian Act on Accounting, the true and fair view. The research methods are based on a synthesis of the national and international literature. The authors examine the regulation system embedded in the legal and economic environment. The paper shows the accounting legislation in Hungary after the changing of the regime, its asymmetry, the attitude of the legislators and the current situation. The analysis of the tax system is connected to the provisions of accounting, highlighting the problems of the tax administration, the relation between corporate tax and the resultsof accounting and the intention to simplify it. The main conclusion is to make the system more flexible, in line with the legal and fiscal institutions, to fulfil its important requirements.